2020
DOI: 10.1002/ijgo.13113
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of postpartum sexual activity and menses among HIV‐infected women on lifelong antiretroviral treatment compared to HIV‐uninfected women in Africa

Abstract: Objective:To determine time from delivery to resumption of sexual activity and menses among HIV-infected women on antiretroviral treatment (ART) and HIV-uninfected women. Methods:HIV-infected women on ART and HIV-uninfected women were recruited from five health facilities at delivery and followed prospectively for a maximum of 1 year in Blantyre, Malawi from January 2016 to September 2017. Sociodemographic, clinical, and laboratory data were collected at delivery and 1.5, 3, 6, 9, and 12 months. Descriptive, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Only 5.6% of those with a sexual problem had pursued medical advice or treatment – Reported sexual problems included: vaginal dryness (16.7% of reported problems), deep dyspareunia (14.9%), vaginal tightness (13.1%), superficial dyspareunia (12.5%), loss of sexual desire (11.9%), vaginal looseness (8.3%), abnormal vaginal discharge (7.1%), vaginal bleeding (4.8%), tiredness (4.8%), and other problems (5.9%) – In multivariate regression, women that had a vaginal delivery were more likely to have reported one or more sexual problems when resuming sex (OR 3.6, p = 0.01); those who had a vaginal laceration or episiotomy were more likely to experience sexual problem(s) when resuming sex (OR 2.4, p = 0.04) Asadi et al (2021) [ 45 ] Iran—Qualitative To explore the experiences related to postpartum changes in women 23 women who have given birth and healthcare providers (midwives and obstetricians) Perception of sexual dysfunction – Postpartum participants described feeling less sexually attractive than in the past, referencing vaginal loosening as a reason, and felt that they were not well-groomed – Some postpartum participants described a decreased feeling of sexual attractiveness (and subsequent self-confidence) in relation to episiotomy scars and the protrusion of labia minora – Some postpartum participants reported that their husband's approval of these appearance changes resulted in greater sexual performance and less anxiety – Postpartum participants also described not enjoying sex because of dyspareunia, as well as due to feelings of burning/dryness, and reported feeling less sexual desire during the postpartum period Borda et al (2010) [ 24 ] 17 DHS countries—Cross-sectional To identify factors affecting return to sexual activity and use of modern family planning among women in the extended postpartum period 15 of 17 countries included all women, two included married women only Resumption of sex – In all 17 countries, women who were 0–2.9 months postpartum reported the least sexual activity – In 13 countries, the majority of women 3.0–5.9 months postpartum had resumed sexual activity and over three-quarters of women 9.0–11.9 months postpartum were sexually active – In 10 countries, exclusive breastfeeding was significantly associated with the woman's resumption of sexual activity, with women currently breastfeeding less likely to have resumed sexual activity at the time of the survey – In 16 countries, resumption of sexual activity was significantly associated with the return of menses. In 14 of these countries, the odds of having resumed sexual activity among women whose menses had returned was more than double the odds of resumption among those whose menses had not returned – Having resumed sexual activity was associated with the duration of the postpartum period (with 0–2.9-month period as referent); in all but Zambia, this association was significant for two or more of the postpartum intervals Dadabhai et al (2020) [ 46 ] Malawi—Prospective Cohort …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 5.6% of those with a sexual problem had pursued medical advice or treatment – Reported sexual problems included: vaginal dryness (16.7% of reported problems), deep dyspareunia (14.9%), vaginal tightness (13.1%), superficial dyspareunia (12.5%), loss of sexual desire (11.9%), vaginal looseness (8.3%), abnormal vaginal discharge (7.1%), vaginal bleeding (4.8%), tiredness (4.8%), and other problems (5.9%) – In multivariate regression, women that had a vaginal delivery were more likely to have reported one or more sexual problems when resuming sex (OR 3.6, p = 0.01); those who had a vaginal laceration or episiotomy were more likely to experience sexual problem(s) when resuming sex (OR 2.4, p = 0.04) Asadi et al (2021) [ 45 ] Iran—Qualitative To explore the experiences related to postpartum changes in women 23 women who have given birth and healthcare providers (midwives and obstetricians) Perception of sexual dysfunction – Postpartum participants described feeling less sexually attractive than in the past, referencing vaginal loosening as a reason, and felt that they were not well-groomed – Some postpartum participants described a decreased feeling of sexual attractiveness (and subsequent self-confidence) in relation to episiotomy scars and the protrusion of labia minora – Some postpartum participants reported that their husband's approval of these appearance changes resulted in greater sexual performance and less anxiety – Postpartum participants also described not enjoying sex because of dyspareunia, as well as due to feelings of burning/dryness, and reported feeling less sexual desire during the postpartum period Borda et al (2010) [ 24 ] 17 DHS countries—Cross-sectional To identify factors affecting return to sexual activity and use of modern family planning among women in the extended postpartum period 15 of 17 countries included all women, two included married women only Resumption of sex – In all 17 countries, women who were 0–2.9 months postpartum reported the least sexual activity – In 13 countries, the majority of women 3.0–5.9 months postpartum had resumed sexual activity and over three-quarters of women 9.0–11.9 months postpartum were sexually active – In 10 countries, exclusive breastfeeding was significantly associated with the woman's resumption of sexual activity, with women currently breastfeeding less likely to have resumed sexual activity at the time of the survey – In 16 countries, resumption of sexual activity was significantly associated with the return of menses. In 14 of these countries, the odds of having resumed sexual activity among women whose menses had returned was more than double the odds of resumption among those whose menses had not returned – Having resumed sexual activity was associated with the duration of the postpartum period (with 0–2.9-month period as referent); in all but Zambia, this association was significant for two or more of the postpartum intervals Dadabhai et al (2020) [ 46 ] Malawi—Prospective Cohort …”
Section: Resultsmentioning
confidence: 99%
“…Studies that examined both positive and negative sexual health outcomes or examined women’s health within the postpartum period from a neutral perspective are outlined within Table 3 [ 24 , 43 68 ] (n = 28). Of note, the majority of studies within this group explore prevalence or corelates of resumption of sex, with little discussion of the positive or negative impact of the timing of sexual activity within the postpartum period [ 24 , 43 , 46 , 48 50 , 53 , 54 , 58 , 61 , 66 , 67 ]. In a multi-country DHS study, resumption of sex was related to the return of a woman’s menses [ 24 ], and this practice was corroborated via qualitative data from Cote d’Ivoire [ 47 ] and Malawi [ 68 ].…”
Section: Resultsmentioning
confidence: 99%